Impaired aerobic work capacity in insulin dependent diabetics with increased urinary albumin excretion. Issue 6633 (14th May 1988) - Jensen, Tonny; Richter, Erik A; Feldt-Rasmussen, Bo; Kelbæk, Henning; Deckert, Torsten
Abstract : To assess whether decreased aerobic work capacity was associated with albuminuria in insulin dependent diabetics aerobic capacity was measured in three groups of 10 patients matched for age, sex, duration of diabetes, and degree of physical activity. Group 1 comprised 10 patients with normal urinary albumin excretion (<30 mg/24 h), group 2 comprised 10 with incipient diabetic nephropathy (urinary albumin excretion 30-300 mg/24 h, and group 3 comprised 10 with clinical diabetic nephropathy (urinary albumin excretion >300 mg/24 h). Ten non-diabetic subjects matched for sex, age, and physical activity served as controls. Oxygen uptake was similar in the four groups at rest and during a 75 W workload. Maximal oxygen uptake was also similar in the control subjects and group 1 (median 41·7, (range 29·1-53·0) ml/kg/min v 38·5 (26·6-59·2) ml/kg/min, respectively), but was significantly lower in group 2 (27·7 (13·9-44·3) ml/kg/min) and group 3 (26·8 (22·6-36·7) ml/kg/min). The difference in maximal oxygen uptake between groups 1 and 2 was 10·8 ml/kg/min (95% confidence interval 3·6 to 23·4 ml/kg/min) and between groups 1 and 3, 11·7 ml/kg/min (4·9 to 22·5 ml/kg/min). These differences were not explained by differences in metabolic control or the degree of autonomic neuropathy. Thus the insulin dependent diabetics with only slightly increased urinary albumin excretion had an appreciably impaired aerobic work capacity which could not be explained by autonomic neuropathy or the duration of diabetes. Whether the reduced capacity is due to widespread microangiopathy or another pathological process affecting the myocardium remains to be established.